Trebonskia zoosporica, gen. et sp. nov., a new member of the Goniochloridales (Eustigmatophyceae, Stramenopiles) with an unusual mode of reproduction. Issue 2 (3rd April 2023) - Přibyl, Pavel; Procházková, Lenka
ABSTRACT: A new freshwater microalgal isolate, CCALA 1135, was characterized using a polyphasic approach (morphology, ultrastructure, fatty acid composition, 18S rRNA gene and rbc L analyses). Non-motile vegetative cells were spherical with thick, smooth cell walls lacking ornamentation, with multiple overlapping chloroplasts and sometimes more than one red globule in the cytoplasm. The nuclear and chloroplast envelopes formed a continuous membrane and there was no pyrenoid. These morphological and ultrastructural features indicated assignment to the class Eustigmatophyceae. The strain was, however, unique in its mode of reproduction: only zoospores were formed, but no autospores were observed (i.e. obligate zoospory, which is rare in the Eustigmatophyceae). The zoospores were relatively fragile and their morphology was similar to those of other members of the clade Goniochloridales (a clade name under the PhyloCode) that have been studied, being uniflagellate and lacking an eyespot. A very high proportion of polyunsaturated fatty acids (up to 57% of total fatty acids) was found, dominated by nutritionally valuable arachidonic and eicosapentaenoic acids, the latter being the most abundant FA (up to 35%) in the total profile. Phylogenetic analysis based on 18S rDNA and rbc L sequences confirmed that CCALA 1135 represents a new member of Goniochloridales clade IIc. Based on cellular morphology, ultrastructure and molecular data we propose this strain as a new species and new genus of the Eustigmatophyceae, Trebonskia zoosporica gen. et sp. nov. Our work is a step toward clarifying the taxonomy of a group of the Eustigmatophyceae with many unnamed strains awaiting characterization. Highlights: A new genus and species of Eustigmatophyceae is described using a polyphasic approach. This isolate reproduces only by zoospores, a mode rare within Eustigmatophyceae. It contained a high proportion of nutritionally valuable polyunsaturated fatty acids.